Ambiguity in the Land Use Component of Mitigation Contributions Toward the Paris Agreement Goals. Issue 8 (4th August 2019) - Fyson, C. L.; Jeffery, M. L.
Abstract: Land use, land use change, and forestry (LULUCF) activities, including deforestation and forest restoration, will play an important role in addressing climate change. Countries have stated their contributions to reducing emissions and enhancing sinks in their Nationally Determined Contributions (NDCs); in 2023, the Global Stocktake will assess the collective impact of these NDCs. Clarity in the contribution of LULUCF to NDC targets is necessary to prevent high LULUCF uncertainties from undermining the strength and clarity of mitigation in other sectors. We assess and categorize all 167 NDCs and find wide variation in how they incorporate LULUCF; many lack the clear information necessary to understand what land‐based mitigation is anticipated. The land sector is included in 121 NDCs, but only 11 provide a LULUCF target that can be fully quantified using information presented or referenced in the NDC. By developing alternative scenarios from a subset of 62 NDCs (89 countries), we estimate that ambiguity in LULUCF contributions causes an uncertainty range in the anticipated LULUCF sink in 2030 of magnitude 2.9 GtCO2eq/year—larger in size than our best estimate for the LULUCF sink of −2 GtCO2eq/year. Clearer communication of data sources and assumptions underlying the contribution of land use to mitigation efforts is therefore important for ensuring a robust Global Stocktake and ambitious emissions reductions. We find that guidance under the Paris Agreement may improve the clarity of future NDCs but is not sufficient to eliminate ambiguities. We therefore recommend that LULUCF targets should be presented and accounted for separately from other sectors. Plain Language Summary: Land‐based activities, including reducing deforestation and planting forests, play an important role in addressing climate change. Under the Paris Agreement, 195 countries agreed to produce national climate change action plans for reducing their emissions. Many of these plans already include land‐based activities, but there is currently no common rule set for how to do so in a scientifically robust way. Our study shows that most national climate action plans are ambiguous in how land‐based activities will contribute to reducing emissions. This makes it difficult to track the role of land‐based activities in global efforts to address climate change and leaves the door open for countries to use uncertain land‐based mitigation to offset emissions from burning fossil fuels. We estimate that this ambiguity causes an uncertainty of 3 GtCO2/year in 2030; this is larger than our estimate of the total human‐made land use sink in 2030 (‐2 GtCO2/year). Recently, countries agreed a set of guidance for how to describe their climate change action plans. This guidance will help to reduce some ambiguity in the role of land‐based mitigation, but it is not sufficient to eliminate ambiguity. We recommend that countries should keep their land‐based mitigation plans separate from targets in other sectors. Key Points: There is a wide variation in how countries include the land sector in their national mitigation contributions under the Paris Agreement Most countries provide an ambiguous land use mitigation target, causing 3 GtCO2/year uncertainty in global land use emissions in 2030 To reduce this uncertainty, countries could clarify their land sector mitigation plans by providing clear and distinct land use targets